Trends and Effects of Psychological and Cognitive Load in Education - Firdaus, Thoriqi; Amelia, Ainunnuril; Alifiyah, Farah Lailatul Nur; Nahdliyah, Afida Silmi; Fausiyeh, Fausiyeh (Journal of Education and Learning Reviews, 2025)
Background and Aim: The cognitive load experienced by students during learning can lead to mental fatigue and significant psychological disturbances, often resulting in negative emotional responses. This study aims to identify trends and examine influential factors in psychological aspects and cognitive load within the educational context, thereby advancing the understanding of educational psychology and cognitive load theory. Materials and Methods: Utilizing a mixed-methods approach, the research integrates bibliometric analysis and a systematic literature review, allowing a comprehensive evaluation of scholarly trends. Research data were sourced from the Scopus database with the keywords "Psychological" AND "Cognitive Load" AND "Education" in article titles, abstracts, and keywords, ensuring alignment with relevant literature. Results: Findings show a fluctuating trend in annual publication citations, marked by phases of notable increases and declines. These patterns are shaped by topical relevance, research quality, and shifts in the academic landscape and technology for information access. The United States leads in publication contributions, comprising 27.4% of total articles, with significant use of terms like cognitive load, learning systems, executive function, and motivation in recent research, while terms like humans, cognition, and education remain consistently emphasized. The insights suggest that innovative learning media, while enhancing outcomes, introduce complexities in managing cognitive load. Conclusion: This study underscores the need for precise cognitive load measurement in developing effective interventions, emphasizing the management of students’ emotions as a critical component in online learning and technology acceptance. These findings inform educational practices and policies by highlighting strategies that support emotional well-being and foster effective, student-centred learning environments, laying the groundwork for future research on enhancing educational practices through cognitive and emotional insights.